The situation of Buddhists' propagation approach of Lao People's Democratic Republic - Vilayphonh, Somsack (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง, 2020)
Buddhism has long been a strong force in Lao culture and remains a major influence in daily life. Buddhism defines the Laotian character. Lao Buddhists belong to the Theravada tradition, based on the earliest teachings of the Buddha Reserved in Sri Lanka after Mahayana Buddhism branched off in the second century B.C. Theravada Buddhism is also the dominant school in Thailand, Cambodia and Myanmar.            Theravada Buddhism was introduced to Luang Prabang in the 13th and early 14th centuries. Mähayana Buddhism may have been introduced in the 8th to 10th centuries but didn't take hold long enough to have a lasting effect. Theravada Buddhism was given a big boost when the King Fa-Ngum, the monarch who unified Laos and created the first Lao Kingdom in the mid 14" century, converted his Kingdom to Buddhism. He built Laos's first wat(temple) in A.D. 1356 to house the Phra Bang Buddha.